Production and characterization of a novel alkaline protease from a newly isolated Neurospora crassa through solid-state fermentation. (March 2020) - Zheng, Liufeng; Yu, Xinying; Wei, Changhao; Qiu, Leyun; Yu, Chenwei; Xing, Qian; Fan, Yawei; Deng, Zeyuan
Abstract: Microbial proteases are widely used to prepare protein hydrolysates with health-promoting biopeptides. Here, a newly isolated strain of Neurospora crassa (named as CGMCC3088) was used to produce proteases through solid-state fermentation of okara as the substrate. The optimal fermentation conditions are: okara, 10 g; water, 21 mL; initial pH, 5.0; incubation temperature, 30 °C; inoculation amount, 2 mL; fermentation time, 72 h, with a corresponding protease activity of 1959.82 U/g. The protease was further purified by ammonium sulphate precipitation, followed by ion-exchange chromatography on DEAE-Sepharose and Sephadex G-75. The molecular weight of the protease was 30 kDa, and further mass spectrometry analysis clearly indicated that it was a novel protease. The protease had the optimal activity at 55 °C and pH 9. The enzyme activity was partially inhibited by SDS and metal ions, whereas little affected by organic solvents. The protease was completely inactivated by phenylmethylsulfonyl fluoride, indicating its dominant serine protease activity. The enzyme preferably hydrolyzed casein, and kinetic analysis showed that its Km and Vmax were 2.18 mg/mL and 36.36 μg/mL/min, respectively. Therefore, Neurospora crassa CGMCC3088 has the potential to produce a novel organic solvent-stable alkaline protease, which may be applied to the preparation of bioactive ingredients. Highlights: Neurospora crassa CGMCC3088 can be treated as a novel functional fermentation organism. Fermentation conditions were optimized for protease producing of Neurospora crassa CGMCC3088. A novel organic solvent-stable alkaline protease was purified from Neurospora crassa CGMCC3088. The purified protease from Neurospora crassa CGMCC3088 can hydrolyze casein, gelatin and hemoglobin.